As especificidades da comunidade religiosa: pessoa e comunidade na obra de Edith Stein - Achilles Goncalves Coelho Junior (2006)
The general objective of this research is to identify the essential aspects of being a community, and being a person, and the relation between them, showing the particularity of the religious communities about their process of becoming themselves, person and the community, based on Edith Steins work. In this theoretical research, Phenomenology was adopted as the theoreticianmethodological foundation in the data collection and the discussion about them. Carrying through a theoretical survey on the subject of the relation between person and community, as well as discussed in Social Psychology, we identify three main perspectives: (a) individualism, (b) sociologism and (c) interactionism. Inserted in the interactionism perspective, Edith Stein initiates the phenomenological analysis from the experiences of the person and, apprehending the different types of experiences, she identifies aspects of the structure of the person that are mobilized at the relation with objects. Then, own body, psyche and spirit, compose the structure of the human being organically related, but this same universal structure is mobilized in distinct ways at men and women. The person lives an unique process of formation where she receives from the community the elements that constitute her personality, at the same time that the person gives to the community her personal being, constituting a proper personality of the community, while she receives the shared reality and acts based on her personal center. The community is apprehended by Stein, in its dynamic aspects, through the way as its members are recognized while people, accepting others positioning and answering to these, solidarity is identified as an essential communitarian experience. The religious experience, identified as a religious sense and natural knowledge of God, faith and mystic experience, moves the persons structure in a specific way, provoking an attention to the reality, a position of opening to reason and the wakening of a way route to the personal center. The free person, the one who lives based on the dynamics of the religious experience, at the same time that receives the world in herself, she also receives religious values, and from her soul, simultaneously, answers to the reality and to God. Specific characteristics of the religious community had been identified to (a) recognition of the humanity as potential religious community; (b) to serve God through the communitarian life; (c) mission of the community and the person conferred by God; (d) freedom and reciprocal responsibility before the common destination. The categories of free person, communitarian personality of the community and experiences, offer a contribution from Edith Steins work, to the discussion of the relation between person and community made for Social Psychology, showing a way for overcoming the dichotomies and for the accomplishment of new studies.